2017
DOI: 10.1080/08037051.2017.1300859
|View full text |Cite
|
Sign up to set email alerts
|

High blood pressure variability predicts 30-day mortality but not 1-year mortality in hospitalized elderly patients

Abstract: Day-to-day BPV is associated with 30-day, but not with 1-year mortality in hospitalized elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Currently, there are no guidelines as to what constitutes a Bsafe^discharge SBP. 1,3,4 In our study, a discharge SBP of 110-140 mmHg was associated with the lowest odds of adverse events in the 30 days post-hospitalization. The odds of 30-day mortality/readmission increased at SBPs < 110 mmHg-with the highest odds observed at SBP values < 80 mmHg.…”
Section: Discussionsupporting
confidence: 47%
“…Currently, there are no guidelines as to what constitutes a Bsafe^discharge SBP. 1,3,4 In our study, a discharge SBP of 110-140 mmHg was associated with the lowest odds of adverse events in the 30 days post-hospitalization. The odds of 30-day mortality/readmission increased at SBPs < 110 mmHg-with the highest odds observed at SBP values < 80 mmHg.…”
Section: Discussionsupporting
confidence: 47%
“…Mean ages of participants ranged from 47.1 years [30] to 85 years. [31] Mean percentage of females in study cohorts was 45.0% (SD: 19.2) with four studies excluding females [2,6,32,33] and one study excluding males. [34] Follow-up interval ranged from 12 months [9,35,36] to 20 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[34] Follow-up interval ranged from 12 months [9,35,36] to 20 years. [37] Thirty-nine studies were conducted in a hospital setting, [4,8,10,11,14,15,19,25,31,[33][34][35][36][38][39][40][41][42][43][44][45][46][47][48][49][50][52][53][54][55][56][57][58][59][60][61]64,69,71] whilst 21 studies were conducted in the community. [1-3,,5,6,9,12,13,16,20,21,30,37,51,62,63,65-68,70] -This was not documented in one paper.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found a correlation between arterial stiffness and mortality in old patients (usually older than 65 years) [ 12 , 13 ] or in those with heart failure with preserved ejection fraction (mean age 75) [ 14 ]. The prognostic impact of BP variability is also controversial in such populations [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%